Sex differences in the effects of social defeat on brain and behavior in the California mouse: insights from a monogamous rodent - Steinman, Michael Q. (Semin Cell Dev Biol, 2016)
Women are nearly twice as likely as men to be diagnosed with major depressive disorder, yet the use of female animal models in studying the biological basis of depression lags behind that of males. The social defeat model uses social stress to generate depression-like symptoms in order to study the neurobiological mechanisms. In general, social defeat is difficult to apply in female rodents. However, male and female California mice (Peromyscus californicus) are territorial. This allows defeat to be studied in both sexes. Males exposed to defeat tend to exhibit proactive coping mechanisms and demonstrate aggression and reduced cognitive flexibility. Females exposed to defeat engage more in reactive coping mechanisms which is highlighted by social avoidance and low aggression. Importantly, effects of defeat on social interaction behavior in females is independent of adult gonadal steroids. These behavioral phenotypes are associated with sex-specific changes in arginine vasopressin (AVP) and oxytocin (OT), closely related peptides that regulate social behavior and stress reactivity. In brain regions associated with stress responses and social behavior, defeat induced long term decreases in AVP activity and increases in OT activity in males and females respectively. Intranasal OT administration was shown to mimic the effects of defeat-induced increases in endogenous OT activity, causing social withdrawal in undefeated females. This suggests that inhibition of OT activity could reduce the impact of stress on behavior in females. These results highlight the value of maintaining diverse rodent models in the search for sex-specific pharmacological approaches to treating mood disorders.